The Septic Neutrophil—Friend or Foe. Issue 2 (February 2021) - Wei, Yibing; Kim, Jiyoun; Ernits, Harri; Remick, Daniel
Abstract : ABSTRACT: Neutrophils play a critical role in the eradication of pathogenic organisms, particularly bacteria. However, in the septic patient the prolonged activation and accumulation of neutrophils may augment tissue and organ injury. This review discusses the different activation states and chemotaxis of neutrophils in septic patients. Neutrophil killing of bacteria and the formation of neutrophil extracellular traps represent important components of the innate immune response and they become dysregulated during sepsis, possibly through changes in their metabolism. Delayed neutrophil apoptosis may contribute to organ injury, or allow better clearance of pathogens. Neutrophils provide a friendly immune response to clear infections, but excessive activation and recruitment has the potential to turn them into potent foes.